Factors affecting outcome and morbidity in pulmonary hydatid cyst surgeries - Ozturk, Bulent; Durkan, Atilla; Eren, Tahir Sevval; Cakmak, Muharrem (Bayrakol Medical Publisher, 2022)
Aim: Hydatid cyst disease is an important health problem due to its endemic, progression, serious complications, and rarely spontaneous regression. Material and Methods: The files of 143 patients who were operated for hydatid cysts in our clinic between January 2000 and December 2010 were analyzed retrospectively. The effects of parameters such as age, gender, symptom, number of cysts, cyst size, whether the cyst is perforated, leukocyte count, and localization of the cyst on mortality and morbidity were investigated. Results: Morbidity rates were high in perforated cysts. However, gender, cyst size, and localization had no effect on morbidity (p<0.05). Discussion: We determined that perforated pulmonary hydatid cysts significantly prolonged hospital stay and increased postoperative morbidity. Pulmonary hydatid disease, which is a public health problem in our country, should be treated surgically when diagnosed.
Keywords: Lung; Hydatid cyst; Morbidity; Perforation